(373) Cost Inflation تكلفة التضخم - Kheir El-Dine, H.; Hansen, B. (supervisor).; Hosny, A. (supervisor). (The Institute Of National Planning., 2018)
During the last few years, the problem of development and inflation has been given much attention. the most important arguments for a certain degree of inflation as prerequisite for development . خلال السنوات القليلة الماضية، حظيت مشكلة التنمية والتضخم باهتمام كبير، وكانت أهم الحجج المؤيدة لوجود قدر معين من التضخم شرطاً أساسياً للتنمية.